Epigenetic regulation of anthocyanin biosynthesis by an antagonistic interaction between H2A.Z and H3K4me3. Issue 1 (30th June 2018) - Cai, Hanyang; Zhang, Man; Chai, Mengnan; He, Qing; Huang, Xinyu; Zhao, Lihua; Qin, Yuan
Summary: The accumulation of anthocyanins in response to specific developmental cues or environmental conditions plays a vital role in plant development and protection against stresses. Extensive research has examined the regulation of anthocyanin biosynthetic genes at the transcriptional and post‐transcriptional levels, but the role of chromatin in this regulation remains unknown. Chromatin immunoprecipitation and quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) analyses were performed. Genetic interactions between trimethylation of lysine 4 on histone H3 (H3K4me3) and the chromatin remodeling complex SWR1 in the control of anthocyanin biosynthesis were further studied. In this study, we provide evidence that a conserved histone H2 variant, H2A.Z, negatively regulates anthocyanin accumulation through deposition at a set of anthocyanin biosynthetic genes and consequently represses their expression in Arabidopsis thaliana . Our data indicate that the accumulation of anthocyanin in H2A.Z deposition‐deficient mutants is associated with increased H3K4me3, which is required for promotion of the expression of anthocyanin biosynthetic genes. We further provide evidence that H3K4me3 in anthocyanin biosynthetic genes is negatively associated with the presence of H2A.Z. Our results reveal an antagonistic relationship between H2A.Z and H3K4me3 in the regulation of the expression of anthocyanin biosynthesis genes, adding another layer of regulation to anthocyanin biosynthesis genes and highlighting the role of chromatin in gene regulation.